Exercising democratic rights and obligations as a mechanism for improved service delivery: The case of Kampala City, Uganada. - Lubinga., S. Nambalirwa (My University, 2014)
Empirical research exploring how the exercise of democratic rights and obligations of citizens impacts on service delivery remains limited and fragmented, leaving little scope for methodical analysis or policy endorsement. Likewise, comparative studies of the factors that account for the deviation in service delivery outcomes at the local level of governance are also somewhat rare and not reflecting the true nature of what is happening in reality. As an example, irrespective of a two decade-plus long prevalence of several democratic participatory frameworks, and the excellent legal and policy frameworks for citizen participation in Kampala, the services rendered to the citizens are still poor. This is not only attesting the statement that participatory initiatives in Uganda are more like wish lists than substantive statements that are guaranteed in practice, but also raising the question: to what extent does the exercise of democratic rights and obligations of citizens by citizen’s impact on public service delivery in Uganda? So, to try and answer this question, this paper applies a quantitative research method were a self-administered questionnaire was distributed to a representative sample of 100 participants. Thereafter, using the ordered logistic regression model of analysis, constructed on the findings the paper divulges that the exercise of democratic rights and obligations of citizens by citizens has a positive implication towards quality service delivery.
Keywords: Democratic rights; Democratic obligations.; Public service; Service delivery; Policy; Citizen participation; Public participation